S84 Is There A Relationship Between Acceptance Of Referral To Smoking Cessation Services Or Pulmonary Rehabilitation And Readmission Rates For Patients With Copd?. (10th November 2014) - Sewell, L; Mitchell-Issitt, C; Barley, K; Chebbout, C; Msimanga, S; Clinch, L; Boyce, S; Steiner, MCS; Singh, SJ
Abstract : Introduction: Readmission to hospital following an acute exacerbation of COPD is a significant burden to patients and health providers. Care bundles are increasingly used to support hospital discharges of patients admitted with an exacerbation of COPD. Referral to smoking cessation, nicotine replacement therapy and pulmonary rehabilitation services are key elements of COPD care bundles but it is not known if uptake to these interventions predicts readmission. Methods: This was a retrospective audit of patients who received a COPD discharge care bundle from April 2012 to March 2014. The care bundle was delivered by the nurse specialists in the Respiratory Discharge Service (REDS). The REDS team follow care bundle patients up for a period of 15 days after hospital discharge. Referral to smoking cessation, Nicotine Replacement Therapy (NRT) and pulmonary rehabilitation services was recorded, along with15 day readmission status as part of usual clinical outcomes. Between group-comparisons were analysed using chi-squared tests with the significance level set at p < 0.05. Results: 15 day readmission status, smoking cessation NRT and PR referral was recorded for 1891 patients (mean (SD) age 71.23 (10.32) yrs, 54.1% male, 40.5% current smokers) who received the care bundle prior to discharge. A total of 269 patients readmitted at 15 days (see table ). There was a significant difference between smoking cessation uptake and readmission status (p = 0.004). There were no between-group differences in respect of readmission status and pulmonary rehabilitation or readmission status and NRT or (p = 0.323 and p = 0.110 respectively). Conclusions: Patients who accept a referral to smoking cessation services following an admission for an exacerbation of COPD may be less likely to readmit to hospital after 15 days but there is no relationship between acceptance of referral to pulmonary rehabilitation and NRT services and 15 day readmission status.